Double trouble? Gag in conjunction with double insert in HIV protease contributes to reduced DRV susceptibility. Issue 2 (31st January 2019) - Williams, Alison; Basson, Adriaan; Achilonu, Ikechukwu; Dirr, Heini W.; Morris, Lynn; Sayed, Yasien
Abstract : HIV protease is essential for processing the Gag polyprotein to produce infectious virions and is a major target in antiretroviral therapy. We have identified an unusual HIV-1 subtype C variant that contains insertions of leucine and asparagine (L38↑N↑L) in the hinge region of protease at position 38. This was isolated from a protease inhibitor naïve infant. Isothermal titration calorimetry showed that 10% less of L38↑N↑L protease was in the active conformation as compared with a reference strain. L38↑N↑L protease displayed a ±50% reduction in K M and k cat . The catalytic efficiency ( k cat / K M ) of L38↑N↑L protease was not significantly different from that of wild type although there was a 42% reduction in specific activity for the variant. An in vitro phenotypic assay showed the L38↑N↑L protease to be susceptible to lopinavir (LPV), atazanavir (ATV) and darunavir in the context of an unrelated Gag. However, in the presence of the related Gag, L38↑N↑L showed reduced susceptibility to darunavir while remaining susceptible to LPV and ATV. Furthermore, a reduction in viral replication capacity (RC) was observed in combination with the related Gag. The reduced susceptibility to darunavir and decrease in RC may be due to PTAPP duplication in the related Gag. The present study shows the importance of considering the Gag region when looking at drug susceptibility of HIV-1 protease variants.